High-dispersion cobalt sulfide and nitrogen-doped carbon-coated cobalt composite material catalyst as well as preparation method and application thereof
Through the preparation of a catalyst for the highly dispersed cobalt sulfide and nitrogen-doped carbon-encapsulated cobalt composite material, the problems of low activity and poor stability of the existing catalysts are solved, and the conversion of H2S and benzonitrile is efficiently achieved, with high activity, low cost and good corrosion resistance.
Patent Information
- Application Number
- CN202510305213.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-06-17
AI Technical Summary
The existing catalysts have problems such as low activity, poor stability, and limited reserves of precious metals when catalyzing H2S reduction of aronitrile compound as thiobenzamide, which limits the further development of catalytic materials.
The catalyst of highly dispersed cobalt sulfide and nitrogen-doped carbon-encapsulated cobalt composite material was prepared by water bath synthesis and hydrothermal in-situ vulcanization methods, and the calcination temperature and hydrothermal in-situ vulcanization temperature were adjusted to control the surface morphology of the catalyst and the concentration of sulfur vacancies.
A catalyst with high activity, high stability and low cost is achieved, which can effectively catalyze the conversion of H2S and benzonitrile to thiobenzamide, improving the catalytic activity of the catalyst and its resistance to hydrogen sulfide corrosion.
Smart Images

Figure CN120155228A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and particularly relates to a highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite material catalyst, and a preparation method and application thereof. Background Art
[0002] Thioamides and their derivatives are an important class of organic compounds and have great application prospects in the fields of fine chemicals, biomedicine, etc. At present, the synthesis of thioamides mainly uses amides and sulfurizing agents (such as carbon disulfide, hexamethyldisilathiane, and elemental sulfur, etc.) for sulfur substitution of oxygen reactions. However, these sulfurizing agent raw materials either have serious pollution in the production process or have problems such as low sulfur atom utilization rate and low conversion efficiency.
[0003] Hydrogen sulfide (H2S) is an important sulfur-containing compound. During the production process of chemical products, a large amount of H2S waste gas will be generated through reactions such as decomposition, synthesis, and combustion, which is likely to cause problems such as catalyst poisoning in the downstream production process, corrosion of pipeline equipment, and environmental pollution. Low-concentration H2S gas has a rotten egg smell, and high-concentration H2S is not easily detected and poses a greater hazard. Therefore, H2S waste gas cannot be directly discharged into the atmosphere. Usually, it is recovered as low-value sulfur, and the contained H element is converted into H2O and discharged as wastewater, resulting in a waste of hydrogen resources. If H2S and the corresponding nitrile are used to undergo an addition reaction to synthesize thioamide compounds. The greatest advantage of this reaction is that it maximally utilizes each atom in the raw material aromatic nitrile compound and H2S molecule, achieving zero waste discharge.
[0004] At present, the solid catalysts that can effectively catalyze the conversion of H2S are mainly supported noble metal (Pt, Pd, Ru, Au)-based and transition metal oxide catalyst systems. However, noble metals have limited reserves and high prices, and traditional carbon material catalysts and transition metal oxide catalysts have problems such as easy poisoning and inactivation, poor cycle stability, and low activity, which limit the further development of the corresponding catalytic materials. Therefore, it is urgent and of great application value and prospect to find a non-noble metal-based catalyst with high activity, high stability, and a simple synthesis route to achieve the nucleophilic addition of H2S to benzonitrile to produce thiobenzamide under mild conditions.
[0005] The core-shell carbon-coated 3d-TMs material catalyst (3d-TMs@C) not only has the advantages of traditional carbon material catalysts, such as large specific surface area, good hydrothermal stability, strong corrosion resistance, and easy surface modification, but also forms a layer of graphite carbon on the surface of the active metal, thereby improving the catalytic stability. In addition, the carbon-nitrogen material carrier also has abundant acid-base sites. Transition metal sulfide catalysts with sulfur vacancy defects can achieve effective activation of the H-S bond. Sulfur vacancies can not only anchor active components and regulate the electronic structure of the catalyst, but also promote the adsorption and activation of reactants (such as H2S and benzonitrile), thereby improving the reaction efficiency.
[0006] Based on this, cobalt sulfide coated with carbon is expected to be used as a catalyst for the reduction of aromatic nitrile compounds by H2S to thio-benzamide. By controlling the calcination temperature, the surface morphology and specific surface area of the catalyst can be regulated, and by controlling the temperature of hydrothermal in-situ sulfidation, the concentration of sulfur vacancies can be regulated, and it is expected to realize the conversion of H2S and benzonitrile into thio-benzamide. Summary of the Invention
[0007] The present invention provides a highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite material catalyst and a preparation method thereof. The synthesis method is simple, has strong repeatability, and can be applied to the reaction of reducing aromatic nitrile compounds by H2S to thio-benzamide.
[0008] A preparation method of a highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite material catalyst. First, a precursor loaded with a cobalt source and having abundant nitrogen and carbon sources is synthesized by a water bath, then Co@CN is obtained by high-temperature calcination in a nitrogen atmosphere, and finally a highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite material catalyst is obtained by a hydrothermal in-situ sulfidation method.
[0009] Furthermore, the preparation method of the highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite material catalyst specifically includes the following steps:
[0010] (1) Dissolve cobalt nitrate hexahydrate in water, and successively add melamine, oxalic acid, and guanine, and stir and mix evenly to obtain a mixed solution;
[0011] (2) Transfer the mixed solution obtained in step (1) to a reaction vessel, naturally cool it to room temperature after hydrothermal complexation reaction, and after centrifugation and drying, obtain a precursor loaded with a cobalt source and having abundant nitrogen and carbon sources;
[0012] (3) Calcinate the precursor obtained in step (2) in a nitrogen atmosphere to obtain the Co@CN precursor;
[0013] (4) Subject the Co@CN precursor obtained in step (3) to a hydrothermal in-situ sulfidation reaction to obtain a highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite material catalyst.
[0014] As a preferred embodiment, the molar ratio of melamine, oxalic acid, guanine and cobalt nitrate hexahydrate in the step (1) is 1:2:1:0.5.
[0015] As a preferred embodiment, the temperature of the hydrothermal complexation reaction in the step (2) is 80 °C and the time is at least 22 h.
[0016] As a preferred embodiment, the temperature of the drying in the step (2) is 60 °C and the time is at least 24 h.
[0017] As a preferred embodiment, the calcination atmosphere in the step (3) is nitrogen, the heating rate is 300 °C / h, and the calcination is carried out at 550 °C for at least 1 h.
[0018] As a preferred embodiment, the sulfur source used in the hydrothermal in-situ sulfidation reaction in the step (4) is thiourea; the molar ratio of the Co@CN precursor to thiourea is 1:1.
[0019] As a preferred embodiment, the temperature of the hydrothermal in-situ sulfidation reaction is 160-200 °C respectively, and the reaction time is at least 12 h.
[0020] The present invention also provides a highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite catalyst prepared by the above preparation method, and the loading amount of Co is 20 wt%.
[0021] The present invention also provides the use of the highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite catalyst in the reaction of H2S and benzonitrile to prepare thiobenzamide.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. In the preparation method of the highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite catalyst provided by the present invention, cobalt nitrate hexahydrate, melamine, oxalic acid and guanine are used as raw materials. Cobalt nitrate hexahydrate forms a complex with melamine, oxalic acid and guanine. When further calcined, the affinity of Co and carbon atoms is moderate, which can catalyze the high-temperature pyrolysis of organic carbon sources, promote the deposition of carbon atoms or carbon clusters on the surface of active metal particles, and obtain a precursor (Co@CN) of metal cobalt supported by a carbon and nitrogen material with abundant acid-base sites. The precursor has more nitrogen vacancies. Then, through hydrothermal in-situ sulfidation, a part of the cobalt source is further converted into the active component Co x S y , and the concentration of sulfur vacancies is regulated by the temperature of hydrothermal in-situ sulfidation to form more sulfur vacancies. The CoxSy active sites with sulfur vacancy defects can effectively activate the H-S bond. The preparation method provided by the present invention is simple and has strong repeatability.
[0024] 2. The highly dispersed cobalt sulfide and cobalt composite catalyst encapsulated by nitrogen-doped carbon prepared by the present invention has more sulfur vacancies and nitrogen vacancies. Sulfur vacancies can not only anchor active components and regulate the electronic structure of the catalyst, but also promote the adsorption and activation of reactants (such as H2S and benzonitrile), thereby improving the catalytic activity of the catalyst; the carbon-nitrogen material carrier has a rich pore structure, which can promote the full contact of H2S, benzonitrile with the active sites of the catalyst, and further improve the catalytic activity; therefore, in the reaction of applying the highly dispersed cobalt sulfide and cobalt composite catalyst encapsulated by nitrogen-doped carbon to catalytic reduction of aryl nitrile compounds by H2S to thio-benzamide, more sulfur vacancies and nitrogen vacancies can promote the adsorption and dissociation of H2S and benzonitrile by the catalyst.
[0025] 3. The highly dispersed cobalt sulfide and cobalt composite catalyst encapsulated by nitrogen-doped carbon prepared by the present invention has a large number of medium-strong basic sites and strong hydrogen sulfide corrosion resistance, which can improve the adsorption capacity for H2S acidic gas, and the raw materials are cheap, the preparation process is simple, and it is easy to realize industrial production, having broad application prospects. Brief Description of the Drawings
[0026] Figure 1 X-ray powder diffraction patterns of CoxSy / Co@CN with different sulfidation temperatures prepared in Examples 1-3 and Comparative Examples and un-sulfided Co@CN;
[0027] Figure 2 N2 adsorption isotherm curves and pore size distribution diagrams of CoxSy / Co@CN with different sulfidation temperatures prepared in Examples 1-3 and Comparative Examples and un-sulfided Co@CN;
[0028] Figure 3 SEM images of CoxSy / Co@CN with different sulfidation temperatures prepared in Examples 1-3 and Comparative Examples and un-sulfided Co@CN;
[0029] Figure 4 TEM image and mapping image of CoxSy / Co@CN-180 prepared in Example 1;
[0030] Figure 5 XPS spectrum of CoxSy / Co@CN-180 prepared in Example 1;
[0031] Figure 6 Catalytic activity comparison diagram of highly dispersed cobalt sulfide and cobalt composite catalyst encapsulated by nitrogen-doped carbon with different sulfidation temperatures prepared in Examples 1-3 and Comparative Examples and un-sulfided Co@CN for catalytic nucleophilic addition of H2S to benzonitrile to prepare thio-benzamide at 70 °C. Detailed Description of the Invention
[0032] The present invention will be further described below in conjunction with preferred embodiments and the accompanying drawings. In the present invention, the endpoints and any values within the disclosed ranges are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.
[0033] The instruments used in the present invention are as follows:
[0034] X-ray powder diffraction (XRD): The phase characterization of the sample was determined using an X'pert3 powder diffractometer. The detector was an X'celerator, and the copper target (Cu Kα, λ = 0.154 nm) was used as the excitation radiation source. The working voltage was 45 kV, and the working current was 40 mA.
[0035] N2 physical adsorption and desorption (N2 Physisorption): The specific surface area, pore distribution, etc. of the sample were determined by N2 physical adsorption. The instrument was a 3Flex fully automatic analyzer produced by Micrometric, USA. The test conditions were as follows: 0.1 g of the sample was weighed, pretreated and degassed at 250 °C for 4 h, cooled to room temperature, and the texture information of the sample was obtained by static adsorption method in a cold trap cooled to -196 °C with liquid nitrogen. The specific surface area and pore size distribution of the sample were calculated according to the BET equation and the BJH model, respectively.
[0036] Scanning electron microscopy (SEM): The morphology of the catalyst was observed by an S-4800 field emission scanning electron microscope. The vacuum degree in the analysis chamber was less than 2.7×10 -6 Pa, and the scanning voltage and current were 5 kV and 7 μA, respectively. The sample powder was adhered to the conductive adhesive and sputter-coated with gold before observation.
[0037] Field emission transmission electron microscopy (TEM): The TEM image of the sample was observed on a JEM-F200 type transmission electron microscope (TEM), and the acceleration voltage was 200 kV.
[0038] X-ray photoelectron spectroscopy (XPS): The surface elemental composition and chemical state of the catalyst were analyzed using an EscaLab 250Xi type spectrometer. The excitation light source was Al target Kα ray, the vacuum degree in the analysis chamber was <10 -8 bar, the excitation power was 22.5 W, and the binding energy of C1s at 284.8 eV was used for calibration.
[0039] The materials, reagents, etc. used in the following examples can be obtained from commercial sources without special instructions.
[0040] Example 1
[0041] This embodiment provides a method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite catalyst, which includes the following steps:
[0042] (1) Dissolve cobalt nitrate hexahydrate in water, and successively add melamine, oxalic acid, and guanine and stir evenly to obtain a mixture; among them, the molar ratio of melamine, oxalic acid, guanine, and cobalt nitrate hexahydrate is 1:2:1:0.5; in this embodiment, 5.84 g of zirconium oxynitrate is dissolved in 200 mL of distilled water, and 5.04 g of melamine, 10.08 g of oxalic acid, and 6.04 g of guanine are respectively added for mixing;
[0043] (2) Transfer the mixture obtained in step (1) to a three-necked flask, react at 80 °C for 22 h, and then naturally cool to room temperature. The solid of the obtained mixture is centrifuged, washed three times each with deionized ethanol and distilled water, and the obtained solid powder is dried at 60 °C for 24 h to obtain a precursor;
[0044] (3) Grind the massive precursor in step (2) into a powder, place it in a tube furnace, heat it to 550 °C at a rate of 5 °C / min, and keep it at a constant temperature for calcination for 1 h to obtain a precursor of carbon and nitrogen material with a disordered mesoporous structure loaded with metallic cobalt (Co@CN);
[0045] (4) Stir the precursor of carbon and nitrogen material with a disordered mesoporous structure loaded with metallic cobalt (Co@CN) obtained in step (3) and thiourea in water for 20 min. The sulfur source used for hydrothermal in-situ sulfidation is thiourea; the molar ratio of Co@CN precursor to thiourea is 1:1; in this embodiment, 1 g of the precursor of carbon and nitrogen material with a disordered mesoporous structure loaded with metallic cobalt (Co@CN) and 2 g of thiourea are added to 60 mL of distilled water and stirred for 20 min; then transferred to a hydrothermal autoclave and reacted at 180 °C for 12 h respectively; after cooling to room temperature, the finally obtained mixture is centrifuged and washed three times with water and absolute ethanol to obtain the final product, a highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite catalyst named CoxSy / Co@CN-180,
[0046] The loading amount of Co in the catalyst CoxSy / Co@CN-180 prepared in this embodiment is 20 wt%.
[0047] From Figure 4 the TEM image and mapping image of CoxSy / Co@CN-180, it can be seen that there are no obvious metal particles in the cobalt sulfide and nitrogen-doped carbon-coated cobalt composite material, and there is no agglomeration phenomenon of metals, oxides, and sulfides, indicating that CoxSy / Co is highly dispersed and modified on the nitrogen-doped carbon support, and at the same time, the distribution of C, O, N, and S in the material is relatively uniform in the whole system.
[0048] From Figure 5 The XPS spectra of CoxSy / Co@CN-180 show that the existing states of Co are mainly metallic cobalt, chelated state, and cobalt sulfide. Combining the analysis of the fine spectra of XPS Co, N, and O indicates that Co is anchored in the material in the form of coordination with O and N, which is consistent with the design goal.
[0049] Comparative example
[0050] In the comparative example, the preparation of the precursor Co@CN of metal cobalt supported on a carbon nitride material with a disordered mesoporous structure without sulfidation was provided. The specific method is as follows:
[0051] (1) Dissolve cobalt nitrate hexahydrate in water, and successively add melamine, oxalic acid, and guanine and stir to mix evenly to obtain a mixture; among them, the molar ratio of melamine, oxalic acid, guanine, and cobalt nitrate hexahydrate is 1:2:1:0.5; in this example, 5.84 g of zirconium oxynitrate is dissolved in 200 mL of distilled water, and 5.04 g of melamine, 10.08 g of oxalic acid, and 6.04 g of guanine are added for mixing respectively;
[0052] (2) Transfer the mixture obtained in step (1) to a three-necked flask, react at 80 °C for 22 h, and then naturally cool to room temperature. The solid of the obtained mixture is separated by centrifugation, washed three times each with sewage ethanol and distilled water, and then the obtained solid powder is dried at 60 °C for 24 h to obtain the precursor;
[0053] (3) Grind the massive precursor in step (2) into a powder, place it in a tubular furnace, heat it to 550 °C at a rate of 5 °C / min, and calcine it at a constant temperature for 1 h to obtain the precursor (Co@CN) of metal cobalt supported on a carbon nitride material with a disordered mesoporous structure.
[0054] Example 2
[0055] The difference between the preparation of the highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite catalyst in Example 2 and Example 1 is that the hydrothermal in-situ sulfidation reaction temperature is 200 °C. Take 1 g of the precursor (Co@CN) of metal cobalt supported on a carbon nitride material with a disordered mesoporous structure and 2 g of thiourea, add them to 60 mL of distilled water and stir for 20 min; then transfer it to a hydrothermal autoclave and react at 160 °C for 12 h respectively.
[0056] Example 3
[0057] The difference between the preparation of the highly dispersed cobalt sulfide and nitrogen-doped carbon-coated cobalt composite catalyst in Example 3 and Example 1 is as follows: the hydrothermal in-situ sulfidation reaction temperature is 200 °C. Take 1 g of the metal cobalt precursor (Co@CN) supported on the disordered mesoporous carbon-nitrogen material and 2 g of thiourea, add them to 60 mL of distilled water, and stir for 20 min; then transfer to a hydrothermal autoclave and react at 200 °C for 12 h respectively.
[0058] Performance Test
[0059] 1. The present invention conducts X-ray powder diffraction tests on CoxSy / Co@CN-180, CoxSy / Co@CN-160, CoxSy / Co@CN-200 with different sulfidation temperatures prepared in Examples 1-3 and the un-sulfided Co@CN prepared in the comparative example. The test method will not be elaborated here. The test results are as Figure 1 shown. Before sulfidation, the diffraction peaks of Co@CN belong to the (004) and (111) crystal planes of carbon. The diffraction peaks of CoxSy / Co@CN with different sulfidation temperatures belong to CoS and Co9S8. Among them, the diffraction peak intensity of CoxSy / Co@CN-180 is stronger, indicating that the sulfidation temperature of 180 °C is most favorable for the formation of CoxSy.
[0060] 2. The present invention conducts N2 adsorption isotherm and pore size distribution tests on CoxSy / Co@CN-180, CoxSy / Co@CN-160, CoxSy / Co@CN-200 with different sulfidation temperatures prepared in Examples 1-3 and the un-sulfided Co@CN prepared in the comparative example. The test method will not be elaborated here. The test results are as Figure 2 shown. The adsorption isotherms of all samples belong to Type IV isotherms and H3-type hysteresis loops. Combining with the pore size distribution diagram, it can be seen that the catalytic materials are mainly mesoporous and macroporous. The pore sizes of the samples show a bimodal distribution, mainly concentrated around 4 nm and 15 nm;
[0061] Table 1 shows the pore structure parameters of CoxSy / Co@CN-180, CoxSy / Co@CN-160, CoxSy / Co@CN-200 with different sulfidation temperatures prepared in Examples 1-3 and the un-sulfided Co@CN prepared in the comparative example, which are specifically as follows;
[0062] Table 1
[0063] carrier <![CDATA[Specific surface area / m 2 .g -1 > <![CDATA[Pore volume / cm 3 .g -1 > Average pore diameter / nm Co@CN 88.4 0.22 6.2 CoxSy / Co@CN-160 42.3 0.18 18.9 CoxSy / Co@CN-180 40.2 0.16 20.7 CoxSy / Co@CN-200 33.7 0.12 24.5
[0064] As can be seen from Table 1, the decrease in specific surface area indicates the formation of more CoxSy active phases.
[0065] 3. The present invention conducts scanning electron microscope tests on CoxSy / Co@CN-180, CoxSy / Co@CN-160, CoxSy / Co@CN-200 with different vulcanization temperatures prepared in Examples 1-3, and unvulcanized Co@CN prepared in the comparative example. The test method will not be elaborated here. The test results are as Figure 3 shown. CoxSy / Co@CN-180 prepared in Example 1, Co@CN prepared in the comparative example, CoxSy / Co@CN-160 prepared in Example 2, and CoxSy / Co@CN-200 prepared in Example 3 are all honeycomb-shaped, with a pore diameter of about 30 nm.
[0066] 4. The present invention tests the catalytic activity of CoxSy / Co@CN-180, CoxSy / Co@CN-160, CoxSy / Co@CN-200 with different vulcanization temperatures prepared in Examples 1-3, and unvulcanized Co@CN prepared in the comparative example for the nucleophilic addition of H2S to benzonitrile to produce thiobenzamide at 70 °C; under the condition of 70 °C, hydrogen sulfide is introduced into the reaction solution (40 mg of catalyst, 4 mmol of reactant benzonitrile, 39 mL of solvent N,N-dimethylacetamide). After reacting for 2 h, its conversion rate and selectivity are calculated; it can be seen from Figure 6 this that the conversion rate and selectivity of preparing methanethiol by CoxSy / Co@CN-180 are the best, indicating that the difference in the content of sulfur vacancies will affect the conversion rate and selectivity of the catalyst for thiobenzamide.
[0067] The above are only the embodiments of the present invention, and do not limit the patent scope of the present invention accordingly. All equivalent structural or equivalent process transformations made by using the content of the specification and drawings of the present invention, or directly or indirectly applied in other related technical fields, are similarly included in the patent protection scope of the present invention.
Claims
1. A method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-wrapped cobalt composite catalyst, characterized in that: Firstly, a precursor loaded with cobalt source and rich in nitrogen source and carbon source was synthesized in a water bath, then Co@CN was obtained by high-temperature calcination in a nitrogen atmosphere, and finally a highly dispersed cobalt sulfide and nitrogen-doped carbon-encapsulated cobalt composite catalyst was obtained by hydrothermal in situ sulfidization.
2. The method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-wrapped cobalt composite catalyst according to claim 1, characterized in that: The specific steps include: (1) dissolving cobalt nitrate hexahydrate in water, and sequentially adding melamine, oxalic acid, and guanine, and stirring to obtain a mixed solution; (2) transferring the mixed solution obtained in step (1) into a reaction container, subjecting the mixed solution to a hydrothermal complexation reaction and then naturally cooling the mixed solution at room temperature, centrifuging the mixed solution and drying the mixed solution to obtain a precursor loaded with a cobalt source and rich in nitrogen and carbon sources; (3) calcining the precursor obtained in step (2) under a nitrogen atmosphere to obtain the Co@CN precursor; (4) The Co@CN precursor obtained in step (3) is subjected to a hydrothermal in-situ sulfurization reaction to obtain a highly dispersed cobalt sulfide and nitrogen-doped carbon-encapsulated cobalt composite catalyst.
3. The method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-wrapped cobalt composite catalyst according to claim 2, characterized in that: In the step (1), the molar ratio of melamine, oxalic acid, guanine and cobalt nitrate hexahydrate is 1:2:1:0.
5.
4. The method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-wrapped cobalt composite catalyst according to claim 2, characterized in that: The temperature of the hydrothermal complexation reaction in step (2) is 80° C. and the time is at least 22 hours.
5. The method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-wrapped cobalt composite catalyst according to claim 2, characterized in that: The drying temperature in step (2) is 60° C. and the drying time is at least 24 hours.
6. The method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-wrapped cobalt composite catalyst according to claim 2, characterized in that: In the step (3), the calcination atmosphere is nitrogen, the heating rate is 300° C. / h, and the calcination is carried out at 550° C. for at least 1 hour.
7. The method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-wrapped cobalt composite catalyst according to claim 2, characterized in that: The sulfur source used in the hydrothermal in-situ sulfurization reaction in step (4) is thiourea; the molar ratio of the Co@CN precursor to thiourea is 1:
1.
8. The method for preparing a highly dispersed cobalt sulfide and nitrogen-doped carbon-wrapped cobalt composite catalyst according to claim 7, characterized in that: The hydrothermal in-situ vulcanization reaction temperature is 160-200° C., and the reaction time is at least 12 hours.
9. A highly dispersed cobalt sulfide and nitrogen-doped carbon-encapsulated cobalt composite catalyst prepared according to the preparation method of any one of claims 1 to 8.
10. The highly dispersed cobalt sulfide and nitrogen-doped carbon-encapsulated cobalt composite catalyst as claimed in claim 9 is used for the reaction of H2S and benzonitrile to prepare thiobenzamide.